Spatial distribution and ecological risk assessment of heavy metals in manganese (Mn) contaminated site - Lv, Yangtao; Kabanda, Gilbert; Chen, Yueru; Wu, Chuan; Li, Waichin (Frontiers in Environmental Science, 2022)
The spatial distribution, migration characteristics and ecological risks of heavy metals in manganese (Mn) contaminated sites were studied by field investigation and geostatistical analysis. In this study, surface soil samples were collected from a Mn mine wasteland and the soil in this area was polluted by Mn, Pb, Cu, Cd, Zn, and Cr, and the corresponding element concentrations were 16.3, 15.4, 15.0, 9.90, 6.10, and 1.1 times of the limited standard, respectively. In addition, the soil in different samples in the same region has obvious heterogeneity. By using X-ray fluorescence spectrometry (XRF) and inductively coupled plasma-mass spectrometry (ICP-MS), the heavy metal concentrations in soil samples were determined. ICP-MS corroborated XRF for soil heavy metal determination and showed that XRF was a reliable and quick alternative for heavy metal determination in soil. To discover heavy metal distribution trends, distribution maps of heavy metals were created using the Kriging interpolation method. The geoaccumulation index (Igeo), improved Nemerow index (INI) and potential ecological risk index (RI) were used to assess the pollution degree and the environmental risk of metal pollution in the study area. The contamination degree of heavy metal is Mn >Cd > Pb > Zn > Cu > Cr. The spatial distribution and risk assessment of heavy metals in manganese contaminated sites will help to monitor the migration trajectory of heavy metals in mining areas and protect the soil from long-term accumulation of heavy metals. It provides basis for heavy metal pollution remediation strategy and ecological risk management.